Análisis de la gestión administrativa en la modalidad distancia virtual por pandemia COVID 19 en la carrera de Agrícola ESPAM MFL - Moreira Navarrete, Junior Jacinto (2022)
The objective of the research was based on analyzing the administrative management of the Agricultural career in the virtual distance modality due to the COVID-19 pandemic to identify potentialities in this modality. For the collection of information, bibliographical, field and exploratory research was used, in addition to the inductive, deductive and analytical-synthetic method for gathering information to verify the components involved. Likewise, an interview was applied to the administrative staff of the ESPAM MFL Agricultural career and a survey to its teaching staff. The investigation procedure had three phases, the first consisted of identifying the structure, functions and competencies of the administrative staff that operates in the Agricultural career of ESPAM MFL, then a comparison of the administrative activities developed in a virtual way and face-to-face in the career and, the perception of the administrative management by the teaching staff in the virtual distance modality was analyzed in the period April / September. 2020. It was evidenced that, in the virtual modality, there was a lack of strengthening the training in the management of technologies, there being a little problem of time and space since the change from the face-to-face modality to the virtual modality was very fast, causing an abrupt change. It was recommended to provide teachers with the facilities to be constantly trained in the use of computer equipment.